Management of the Thrombosed Filter-Bearing Inferior Vena Cava - Sildiroglu, Onur (Thieme Medical Publishers, 2012)
Inferior vena cava (IVC) filter thrombosis is a complex problem. Thrombus within an IVC filter may range from an asymptomatic small thrombus to critical IVC occlusion that affects both lower extremities. The published experience of IVC thrombosis management in relation to filters is either anecdotal or limited to a small group of patients; however, endovascular treatment methods appear to be safe and effective in patients with IVC thrombosis. This review focuses on filter-related IVC thrombosis and its endovascular management.